THE ROLE OF NAHDLATUL ULAMA IN ACCELERATION HALAL CERTIFICATION IN THE ECONOMIC AND BUSINESS - Alfigora Syahputra; Pardiman Pardiman; Nurhidayati Nurhidayati (Reflektika, 2021)
This article discusses the role of the most prominent Islamic organization in Indonesia, namely Nahdhatul Ulama, in accelerating halal certification. Based on the study results, it can be concluded that the halal certification agency played by Nahdhatul Ulama' has no other purpose than its establishment, namely the existence of a benefit. Maslahah mursalah is the proper basic concept taken to provide certainty of the status of the NU Halal Agency halal certification agency with authority to carry out halal certification. This can be confirmed by lying in the kulliyatul al-khamsah, namely: protection of religion, soul, reason, protection against descent and of property.